Pengaruh Model Pembelajaran NHT Berbantuan Media Pembelajaran Interaktif Terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Akuba, Wahyuni; Machmud, Tedy; Takaendengan, Bertu Rianto (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
This study investigates the impact of the cooperative learning model Numbered Heads Together (NHT) combined with interactive learning media on the mathematical problem-solving ability of eighth-grade students. The research aims to address the prevalent low levels of problem-solving competence among students by implementing an innovative student-centered learning approach. Using a quasi-experimental design with a post-test only control group, this study involved two classes selected through random sampling at SMP Negeri 1 Kwandang, with 30 students in each group. The experimental group received the NHT learning model supported by interactive media, while the control group was taught using a direct instruction method with the same media. Data were collected through validated problem-solving tests, analyzed using independent sample t-tests, normality and homogeneity tests, and effect size calculations. The results demonstrated a significant difference between the two groups, with the experimental group achieving higher problem-solving scores (mean score of 32.6 versus 27.9) and a high effect size (Cohen's d = 0.9032). These findings suggest that integrating NHT with interactive learning media effectively enhances students' mathematical problem-solving skills by fostering active engagement, collaboration, and conceptual understanding. The study highlights the importance of adopting interactive, student-centered learning models to improve mathematics education outcomes.